2014
DOI: 10.1371/journal.pone.0086124
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondria in Parvovirus Pathology

Abstract: Proper functioning of the mitochondria is crucial for the survival of the cell. Viruses are able to interfere with mitochondrial functions as they infect the host cell. Parvoviruses are known to induce apoptosis in infected cells, but the role of the mitochondria in parvovirus induced cytopathy is only partially known. Here we demonstrate with confocal and electron microscopy that canine parvovirus (CPV) associated with the mitochondrial outer membrane from the onset of infection. During viral entry a transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 73 publications
1
20
1
Order By: Relevance
“…CPV-2a infection significantly activates host immune response-related signaling and CPV-2a is another potential immune cell activator, although further research is needed to investigate the effect on other cells lines and the underlying mechanisms. Yet, some studies mentioned that CPV-2a induces apoptosis [15,17], but our gene profiling data showed no connection between CPV-2a infection and apoptosis, which may be attribute to the virus types. This work extends our knowledge of CPV-2a-mediated cell infection and regulation.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…CPV-2a infection significantly activates host immune response-related signaling and CPV-2a is another potential immune cell activator, although further research is needed to investigate the effect on other cells lines and the underlying mechanisms. Yet, some studies mentioned that CPV-2a induces apoptosis [15,17], but our gene profiling data showed no connection between CPV-2a infection and apoptosis, which may be attribute to the virus types. This work extends our knowledge of CPV-2a-mediated cell infection and regulation.…”
Section: Discussioncontrasting
confidence: 60%
“…VP2 is the main component to determine host range and mediate virus-receptor interaction during CPV-2 infection [13,14]. Parvovirus infection causes different effects on host cells, which depend on the species of virus and the cell lines [15]. CPV-2 is involved in induction of apoptosis in several cell lines, including Madin-Darby canine kidney (MDCK) cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors provide electron microscopic visuals of abnormal mitochondrial phenotypes that are similar to the ones we have included in our results including heterogeneously swollen mitochondria, membrane blebbing and disappearance of cristae. 58 Notably, the authors indicate activation of MEK/ERK signaling resulting from mitochondrial dysfunction in Parvovirus infection. We have previously demonstrated that VEEV infection leads to robust activation of the MEK/ERK signaling cascade, which is important for the virus to establish a productive infection.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of STAT-3 lead to the down-regulation of p53 [31] and hence, this may be a mechanism, by which B19 compromises the regulation of energy production within infected cells. The presence of NS1 leads to mitochondrial depolarization and elevated ROS production, which persists throughout the period of infection [119,120]. There is also evidence of decreased mitochondrial numbers in infected cells [121], which may reflect the fact that the survival of B19-infected cells is enabled by increased mitochondrial autophagy [122].…”
Section: Parvoviridaementioning
confidence: 99%